Economic Governance of the Democratic Republic of Vietnam through Domestic Trade (1945–1954) - Vuong, Pham Thi (Social Lens, 2026)
This article analyzes the economic governance activities of the Democratic Republic of Vietnam through the field of domestic trade during the period 1945–1954. Based on an examination of the State's guidelines, policies, and practices in organizing and managing the circulation and distribution of goods, the article clarifies the process by which the Democratic Republic of Vietnam gradually established and developed mechanisms for governing domestic trade in accordance with the prevailing economic conditions and the requirements of the resistance war. Domestic trade not only contributed to restoring and maintaining the operation of the domestic market but also served as an important instrument for the Democratic Republic of Vietnam to regulate the circulation of goods, stabilize prices, and mobilize and allocate resources for production, people's livelihoods, and the resistance war. Through the management of domestic trade, the Democratic Republic of Vietnam gradually strengthened its capacity to organize, regulate, and control economic relations, thereby contributing to securing resources for the resistance war, strengthening the autonomy of the economy, and laying the initial foundations for state economic governance capacity under wartime conditions.
Keywords: economic governance; domestic trade; democratic republic of Vietnam; state capacity